Qualitative and quantitative chemical analysis of Leptadenia hastata: exploring a traditional african medicinal plant - Zhang, Jiangsheng; Nan, Yi; Su, Jie; Jibril, Aminu Usman; Lv, Guiyuan (Frontiers in Chemistry, 2024)
Leptadenia hastata (Pers.) Decne is a commonly used food source and prescribed as a traditional African medicine for treatment of various diseases, such as diabetes, skin disorders, wounds, and ulcers. However, quality control has become a bottleneck restricting the therapeutic development and utilization of this plant. In this study, a reliable method for qualitative and quantitative determination of components in L. hastata was established. The components of L. hastata were profiled using ultra-high performance liquid chromatography coupled with quadruple time-of-flight tandem mass spectrometry (UHPLC-Q-TOF-MS). Subsequently, an ultra-high performance tandem diode array detector (UHPLC-DAD)-based method was used for simultaneous quantitative analysis of five major constituents in six batches of L. hastata samples. As a result, 35 compounds were tentatively identified. The quantities of the five constituents (vicenin-Ⅱ, orientin, schaftoside, chrysin 6-C-arabinoside 8-C-glucoside, chrysin 6-C-glucoside 8-C-arabinoside) were determined as 124.8-156.9 μg/g, 170.5-216.0 μg/g, 61.31-93.73 μg/g, 85.13-119.3 μg/g and 99.82-129.4 μg/g, respectively. This method offers a successful strategy for precise and effective evaluation of the constituents of L. hastata, providing a robust foundation for holistic quality assessment of medicinal plants.